Supervision and Fuzzy Control of a Manufacturing Process using LabVIEW - Zermane Hanane (IEEE 5th International Conference on Electrical Engineering – Boumerdes, Algeria, 2017)
Presently, in industrial process plants, requirements for Continuous Emission Monitoring (CEM) have increased significantly. Most plants are investing in these systems in order to burn waste. In this work, we developed a Fuzzy Control of CEM (FCCEM). This system contains operator's stations to supervise the bag filter using Fuzzy Logic. This equipment consists of a suction ventilator, a bag filter and a system for collecting and evacuating the dust. To optimize the running of the bag filter workshop and ensure continuous control, the process based on fuzzy logic involves the removal or filtration of smoke from the kiln and/or raw mill with control of temperature and pressure of fumes.